Pengaruh LKPD berbasis Discovery Learning terhadap Kemampuan Literasi Sains Mahasiswa - M. Misbachul Huda; Heri Miarto; Ahmad Rif'an Najih (STKIP AL HIKMAH SURABAYA, 2024)
The aim of this research is to determine the effect of Discovery Learning-based Student Worksheets (LKPD) on students' scientific literacy abilities. The type of research used is a pre-experimental design with one group pretest-posttest. Data collection was carried out by testing students' literacy abilities. The test instrument was prepared by emphasizing three aspects of scientific literacy, namely concepts, processes, and scientific context. The research sample was students of PGSD STKIPAL Hikmah Surabaya. Hypothesis testing was carried out using a paired sample t-test assisted by the SPSS program. The swimmer test carried out was a normality test using the Shapiro-Wilk test. The research results show that Discovery Learning-based LKPD has an effect on students' scientific literacy abilities. The research results show that aspects of learning, such as learning models, learning resources, and the existence of LKPD, can influence students' scientific literacy abilities.